Country programmable aid : differences, divergences and contradictions between donor aid strategies and beneficiary country developments plans - O'Riordan, Alexander (School of Economics, 2016)
Aid has a significant impact on governance and public spending in sub-Saharan Africa. In Mozambique (amongst others) aid accounts for more public spending than domestic revenues do. Even in countries less dependent on aid, international donors influence policy making by investing in a technical competitive advantage over domestic policy makers in sectors ranging from climate financing to resilience and public financial management. This doubly affects South Africa both because South Africa is a large recipient of international donor aid and because South Africa is an international donor in its own right in sub-Saharan Africa. The problem is that how international donors set their priorities and allocate their aid at country level is not sufficiently answered in the literature. International donors are seen by many as unpredictable even though they have an outsized influence on domestic policy and spending and are not accountable to the sub-Saharan voters. This research project contributes to the literature on the political economy of donor allocations of aid in sub-Saharan Africa. The research approach focuses on country programmable aid, EU joint programming and donor country strategy papers. The foundation is comparing and contrasting international donors stated policies on 'country programmable aid' with what transpires in practice. Key entry points were the relationship between donor country strategies and the beneficiary country's national development plan, and the extent to which donors made use of political economy and or context analysis and analysis of sector strategies. The key findings are that there are (and what might even be predictable) patterns in how donors programme their aid at country level, not explained by the particular context nor accounted for in the beneficiary country's national development plan. These patterns relate to a tendency to decontextualize aid programming accompanied with a narrative of donor moral and technological superiority and unrealistic programming objectives. The finding is important because it implies that these patterns result from implicit rules governing how international donors allocate aid, thus making them predictable features of an aid relationship, wanted or unwanted consequences of giving aid.